Експериментальне дослідження технології вібраційного подрібнення - Рудь, В. Д.; Гальчук, Т. Н.; Божко, Т. Є. (НТУ "ХПІ", 2014)
Експериментально перевірено, що найоптимальнішим для металічного порошку є подрібнення у млині із зміщеною віссю обертання у разі накладання вібрації. В результаті пришвидшується процес подрібнення в 1,5 – 2 рази за рахунок стираючої та ударної сили розмельних тіл. Подрібнення проводили в лабораторному млині спеціальної конструкції. В якості досліджуваного матеріалу використані металеві порошки сталі ШХ15.

Grinding was carried out in a laboratory mill special design. The new laboratory setup, a comparative study of two methods of grinding metal powders: rotational method and vibroobertalnyy with direct and oblique axis of rotation. The proposed grinders sold almost all methods of destruction, but there is a major shock-obliterative It was verified experimentally that the most optimal conditions for metal powder is grinding in a mill with offset axis of rotation upon application of vibration. As a result, the process of grinding acceler-ates in 1,5–2 times due to erasing and a strike force of grinding bodies. As a result, the powder is evenly dis-tributed by fractions. As the investigated material used metal powders steel SHH15. As an grinding of bodies been used made of steel the balls with a diameter of 23 mm and 32 mm. The mass ratio of of powder and balls of 1:0,75.Grinding was carried out in a laboratory mill special design. The new laboratory setup, a comparative study of two methods of grinding metal powders: rotational method and vibroobertalnyy with direct and oblique axis of rotation. The proposed grinders sold almost all methods of destruction, but there is a major shock-obliterative It was verified experimentally that the most optimal conditions for metal powder is grinding in a mill with offset axis of rotation upon application of vibration. As a result, the process of grinding acceler-ates in 1,5–2 times due to erasing and a strike force of grinding bodies. As a result, the powder is evenly dis-tributed by fractions. As the investigated material used metal powders steel SHH15. As an grinding of bodies been used made of steel the balls with a diameter of 23 mm and 32 mm. The mass ratio of of powder and balls of 1:0,75.
Experimental study of vibrating grinding of technology
Keywords: металообробна промисловість; металічний порошок; вібрація; млин; гранулометричний склад; vibration; mill; metal powder; grinding